THE EFFECTIVENESS OF USING HERRINGBONE TECHNIQUE TO TEACH READING COMPREHENSION OF NARRATIVE TEXT - Rahmawati, Sumi; Sudarsono, Sudarsono; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to find out whether or not the Herringbone technique affected the teaching of reading comprehension of narrative text significantly to Year – 10 students of SMKN 03 Pontianak in Academic Year 2018/2019. This research was pre-experimental design with pre-test, post-test and three times of treatments. The data were collected through a multiple-choice test. The sample of the research was taken from Year – 10 AP4 classes which consist of 30 students. The finding showed that the mean score of the students’ pre-test was 66 while the post-test was 86. It showed that the achievement of the students increased after the treatment was conducted. In this research, the researcher used the t-table a (0.05) with a degree of freedom 29 is 1.699 meanwhile, the result of the t-test is 9.70 it means the t-test was higher than the t-table (9.70 > 1.699). The result of the effect size (ES) was 1.82 which was categorized as a strong effect. It showed that the null hypothesis was rejected and the alternative hypothesis was accepted. It proved that the Herringbone technique affects significantly the students’ reading comprehension of narrative text.Keywords: Reading Comprehension, Narrative Texts, Herringbone Technique.